Joint analysis of D-dimer, N-terminal pro b-type natriuretic peptide, and cardiac troponin I on predicting acute pulmonary embolism relapse and mortality - Xiaoyu Liu (Nature Portfolio, 2021)
Abstract Previous studies on the adverse events of acute pulmonary embolism (APE) were mostly limited to single marker, and short follow-up duration, from hospitalization to up to 30 days. We aimed to predict the long-term prognosis of patients with APE by joint assessment of D-dimer, N-Terminal Pro-Brain Natriuretic Peptide (NT-ProBNP), and troponin I (cTnI). Newly diagnosed patients of APE from January 2011 to December 2015 were recruited from three hospitals. Medical information of the patients was collected retrospectively by reviewing medical records. Adverse events (APE recurrence and all-cause mortality) of all enrolled patients were followed up via telephone. D-dimer > 0.50 mg/L, NT-ProBNP > 500 pg/mL, and cTnI > 0.40 ng/mL were defined as the abnormal. Kaplan–Meier curve was used to compare the cumulative survival rate between patients with different numbers of abnormal markers. Cox proportional hazard regression model was used to further test the association between numbers of abnormal markers and long-term prognosis of patients with APE after adjusting for potential confounding. During follow-up, APE recurrence and all-cause mortality happened in 78 (30.1%) patients. The proportion of APE recurrence and death in one abnormal marker, two abnormal markers, and three abnormal markers groups were 7.69%, 28.21%, and 64.10% respectively. Patients with three abnormal markers had the lowest survival rate than those with one or two abnormal markers (Log-rank test, P < 0.001). After adjustment, patients with two or three abnormal markers had a significantly higher risk of the total adverse event compared to those with one abnormal marker. The hazard ratios (95% confidence interval) were 6.27 (3.24, 12.12) and 10.7 (4.1, 28.0), respectively. Separate analyses for APE recurrence and all-cause death found similar results. A joint test of abnormal D-dimer, NT-ProBNP, and cTnI in APE patients could better predict the long-term risk of APE recurrence and all-cause mortality.